PROSES BERPIKIR KREATIF SISWA SMP DALAM MENYELESAIKAN MASALAH SISTEM PERSAMAAN LINEAR DUA VARIABEL BERDASARKAN TEORI WALLAS - Shinta Aplian Tarusu; Mahmuddin Yunus; Shinta Aplian Tarusu (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
The purpose of this qualitative descriptive study is to describe how junior high school students apply Wallas theory to solve problems involving a two-variable linear equation system (SPLDV). The main data in this study came from the results of written tests and subject interviews. Three students of class VIII-I from SMP Negeri 19 Malang became the research subjects. Subject selection is based on the process of solving the test questions given based on the indicators of Wallas' theory. In addition, good oral communication skills are required for further interviews. The instrument in this study consisted of one SPLDV story question and a validated interview guide. Source/data triangulation techniques and methods were used to validate this research data. The results showed that overall, students' creative thinking abilities were very diverse. There are students who are able to pass 3 stages of creative thinking. However, there are students who are only able to pass 2 stages. There are even students who only pass 1 stage of Wallas creative thinking. So it can be said that the creative thinking process of students is still relatively low. Students are able to draw conclusions correctly, but students' creative thinking processes according to the creative thinking stage of Wallas' theory are still not able to be passed properly, especially at the preparation and verification stages.